Improving the reliability performance of medium voltage networks - Khan, Zahir Hoosain (Department of Electrical Engineering, 2016)
The aim of this dissertation is to investigate alternative, more reliable and cost effective ways of improving the reliability performance of medium voltage networks. Customers are mainly affected by faults on the distribution MV network, to which, consequently, we have to pay particular attention. A major requirement on electricity supply systems is high supply reliability for the customer which is mainly determined by the distribution networks. Power system reliability is an essential factor in the quality of supply and is directly related to the number and duration of outages. By analysing the power system properly, the weaknesses will then be identified and improvements can be introduced to minimise the occurrence of outages. A decrease in the outage rate will result in an improvement in reliability and quality of supply of the distribution MV network. The dissertation focuses on improving the network management by increasing the level of network automation and control which improves the operating efficiency of medium voltage distribution networks. Steps are shown how to equip the network according to progressive investment capability, from Fault Path Indicators (FPIs) and remote control Pulseclosing technologies to automatic FuseSavers and Tripsavers used in a feeder automation scheme to minimise the number of disturbances and the outage durations experienced when they occur. The results of a study analysing the impact of different intelligent automation solutions on the reliability performance of Medium Voltage distribution networks are presented in the dissertation. The respective system topologies are modelled and the resulting system reliability performance is determined by reliability calculations such as the SAIDI and SAIFI values. The results show that the distribution automation technologies can have a very significant impact on both the SAIDI and SAIFI performance of the systems. Further, selected details related to the implementation of such intelligent automation schemes are presented in this dissertation.